Iron nanoparticles based nanofluids for in situ environmental remediation - Crespi, Julieta; Binetti Basterrechea, Gian Franco; Finoli, Agostina Sol; Montesinos, Victor Nahuel; Quici, Natalia (Oscar Pagola (Asociación Argentina de Ingenieros Químicos), 2024)
In this work, stabilization of commercial nZVI (NANOFER STAR, hereafter NSTAR, provided by NANOIRON s.r.o.) with carboxymethyl cellulose (CMC) was studied. NFs prepared with CMC (CMC-NSTAR) were compared and with NFs prepared without CMC (b-NSTAR). Stabilization was evaluated by sedimentation rate analysis of the nanoparticles in CMC-NSTAR versus b-NSTAR. The mobility of both stabilized and non-stabilized NFs was studied in columns filled with porous media at laboratory and pilot scale. NFs were injected upwards in the column with a peristaltic pump, and the nZVI concentration was monitored with turbidity measurement at the outlet stream. Then, NFs reactivity for the removal of aqueous Cr(VI) was tested in batch and columns experiments. In the batch experiments, 15 mg L-1 Cr(VI) solutions and the NFs were mixed with an orbital shaker, with a Fe:Cr molar ratio = 10. In the column experiments, a porous media bed was loaded with 0.5 g of n-NSTAR and then a 100 mg L-1 Cr(VI) solution was injected upwards.
Keywords: nanomateriales; remediación ambiental; nanopartículas de hierro cerovalente; nanofluidos; Cr(VI)